The usage of biological system for potato protection from Colorado potato beetle (Leptonotarsa decemlineata Say.) and late blight (Phytophthora infestans (Mont) de Bary) - Solomiychuk, M.; Kordulyan, Yu. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2018)
The results of research and practical use of biological products in different schomes of potato protection are presented from Colorado potato beetle and late blight. The Colorado potato beetle’s season dynamics was observed. The insecticide’s actions efficiency against Colorado potato beetle’s imaho and larva during the sowing spray was shown. The biological fungicides and insecticides combination impact was researched in potato treating complexes against pest and late blight appearing. The biological preparations usage together with preparations of chemical origin for tubers treating was favoured significantly potato yield enlargement and it’s quality increase.